A comprehensive analysis of factors related to carmustine/bevacizumab response in recurrent glioblastoma (2019)
Purpose Patients with recurrent glioblastoma (rGBM) have a poor prognosis, with survival ranging from 25 to 40 weeks. Antiangiogenic agents are widely used, showing a variable response. In this study, we explored the efcacy of carmustine plus bevacizumab (BCNU/Bev) for treating rGBM. Methods/patients In this study, we assessed 59 adult patients with histologically confrmed rGBM who were treated with BCNU/Bev as second-line regimen. The response rate (RR), progression-free survival (PFS) and overall survival (OS) were evaluated according to their molecular expression profle, including CD133 mRNA expression, MGMT methylation (pMGMT), PDGFR amplifcation, YKL40 mRNA expression, IDH1/2 condition, p53 and EGFRvIII mutation status. Results Median follow-up was 18.6 months, overall RR to the combination was 56.3%, and median PFS was 9.0 months (95% CI 8.0–9.9). OS from time of diagnosis was 21.0 months (95% CI 13.2–28.7) and from starting BCNU/Bev it was 10.7 months (95% CI 9.5–11.8). IDH1/2 mutations were found in 30.5% of the patients, pMGMT in 55.9% and high CD133 mRNA expression in 57.6%. Factors which positively afected PFS included performance status (p=0.015), IDH+ (p=0.05), CD133 mRNA expression (p=0.009) and pMGMT+ (p=0.007). OS was positively afected by pMGMT+ (p=0.05). Meanwhile, YKL40 negatively afected PFS (p=0.01) and OS (p=0.0001). Grade≥3 toxicities included hypertension (22%) and fatigue (12%). Conclusions BCNU/Bev is a safe and tolerable treatment for rGBM. Patients with MGMT+/IDH+ derive the greatest beneft from the treatment combination in the second-line setting. Nonetheless, high YKL40 expression discourages the use of antiangiogenic therapy.